VOSA: SED building and analysis of thousands of stars in the framework of Gaia. Issue 67 (17th July 2015) - Rodrigo, C.; Solano, E.; Bayo, A.
Abstract : VOSA (http://svo2.cab.inta-csic.es/theory/vosa/ ), is a web-based tool designed to combine private photometric measurements with data available in VO services distributed worldwide to build the observational spectral energy distributions (SEDs) of hundreds of objects. VOSA also accesses various collections of models to simulate the equivalent theoretical SEDs, allows the user to decide the range of physical parameters to explore, performs the SED comparison, provides the best fitting models to the user following two different approaches (chi square and Bayesian fitting), and, for stellar sources, compares these parameters with isochrones and evolutionary tracks to estimate masses and ages. In particular, VOSA offers the advantage of deriving physical parameters using all the available photometric information instead of a restricted subset of colors. VOSA was firstly released in 2008 and its functionalities are described in Bayo et al. (2008). At the time of writing there are more than 300 active users in VOSA who have published more than 60 refereed papers. In the framework of the GENIUS (https://gaia.am.ub.es/Twiki/bin/view/GENIUS ) project we are upgrading VOSA to, on one hand, provide a seamless access to Gaia data and, on the other hand, handle thousands of objects at a time. In this poster, the main functionalities to be implemented in the Gaia context will be described. The poster can be found at:http://svo.cab.inta-csic.es/files/svo//Public/SVOPapers/posters/vosa-poster3.pdf.